The effect of specific exercises on a training apparatus designed to develop certain motor abilities and improve skill performance on the parallel bars in advanced artistic gymnastics - Majeed, Asst.L.Fatima Haider; Awad, Prof. Dr. Jumaa Muhammad; Nasser, L.Dr. Salman Ahmed; Hammadi, L.Dr. Jassim Nafie (Sulaimani Journal for Humanities, 2026)
This research aims to design a training apparatus and specific exercises for it, and to determine the effect of these exercises on developing certain motor skills and improving skill performance on the parallel bars in advanced artistic gymnastics. The researchers hypothesized statistically significant differences between pre- and post-test results in certain motor skills and parallel bars skills for advanced artistic gymnastics. The researchers employed an experimental design with a single experimental group using pre- and post-tests. The research sample consisted of five (5) male members of the national advanced artistic gymnastics team, aged 17-19 years, for the 2023-2024 training season. The specific exercises were implemented on the designed training apparatus in three training sessions per week, on Sundays, Tuesdays, and Thursdays, for a total of 30 training sessions distributed over 10 weeks. The main experiment was conducted on Thursday, November 16, 2023, at 4:00 PM in the national team's indoor gymnastics hall. In artistic gymnastics, up until Tuesday, January 23, 2024, after the experiment was completed and the results were obtained, the researchers concluded that the use of special exercises on the designed training apparatus had a positive effect on the development of motor abilities, and also had a positive effect on the development of parallel bars skills in artistic gymnastics.
Keywords: Special exercises; designed training equipment; motor skills; parallel bars